In vitro and in silico analysis of the Anopheles anticholinesterase activity of terpenoids. (April 2023) - Rants'o, Thankhoe A.; Koekemoer, Lizette L.; van Zyl, Robyn L.
Abstract: Anopheles gambiae, An. coluzzii, An. arabiensis, and An. funestus are major vectors in high malaria endemic African regions. Various terpenoid classes form the main chemical constituent repository of essential oils, many of which have been shown to possess insecticidal effects against Anopheles species. The current study aimed to assess the bioactivity of terpenoids including four sesquiterpene alcohols, farnesol, (-)-α-bisabolol, cis -nerolidol, and trans -nerolidol; a phenylpropanoid, methyleugenol, and a monoterpene, ( R )-(+)-limonene, using the larvicidal screening assay against the four Anopheles species. The mechanism of action was investigated through in vitro acetylcholinesterase inhibition assay and in silico molecular modelling. All six terpenoids showed potent larvicidal activity against the four Anopheles species. Insights into the mechanism of action revealed that the six terpenoids are strong AChE inhibitors against An. funestus and An. arabiensis, while there was a moderate inhibitory activity against An. gambiae AChE, but very weak activity against An. coluzzii. Interestingly, in the in silico study, farnesol established a favourable hydrogen bonding interaction with a conserved amino acid residue, Cys 447, at the entrance to the active site gorge. While (-)-α-bisabolol and methyleugenol displayed a strong interaction with the catalytic Ser 360 and adjacent amino acid residues; but sparing the mutable Gly 280 residue that confers resistance to the current anticholinesterase insecticides. As a result, this study identified farnesol, (-)-α-bisabolol, and methyleugenol as selective bioinsecticidal agents with potent Anopheles AChE inhibition. These terpenoids present as natural compounds for further development as anticholinesterase bioinsecticides. Highlights: Essential oils prove to be a potential source of bioinsecticides for malaria vector control. Select essential oil constituents showed potent larvicidal activity against four main African malaria vectors. These terpenoids also exhibilted selective  Anopheles  acetylcholinesterase inhibitory activity.